1996
DOI: 10.1080/11250009609356123
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and overlap of the diet of seven passerine trans‐saharian migrants during spring stopover at two mediterranean sites

Abstract: (1996) Consistency and overlap of the diet of seven passerine trans-saharian migrants during spring stopover at two mediterranean sites, Italian Journal of Zoology, 63:2,[149][150][151][152][153][154][155][156] Zool., 63: 149-155 (1996) Consistency and overlap of the diet of seven passerine trans-saharian migrants during spring stopover at two mediterranean sites ABSTRACTThe diet of seven passerine trans-saharian migrant species was analysed by means of faecal analysis during their spring passage at an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…We found that similar species have diets that overlap in composition (Marchetti et al 1996). M A R C H E T T I E T A L .…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…We found that similar species have diets that overlap in composition (Marchetti et al 1996). M A R C H E T T I E T A L .…”
mentioning
confidence: 64%
“…However, other groups, such as aphids, vary in importance in the birds' diets and add to differentiation (Marchetti et al 1996). However, other groups, such as aphids, vary in importance in the birds' diets and add to differentiation (Marchetti et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The younger the nestlings are, the softer food they are given (Pruska, 1980), and thus aphids are likely suitable prey items for young nestlings. Adult pied flycatchers may also eat aphids (Marchetti et al, 1996). Older nestlings are also given harder food items, such as ants (Meidell, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Adult birds and older nestlings consume larger and harder arthropods than younger nestlings (Silverin and Andersson, 1984). Ants, beetles and aphids were the most common food sources of adult pied flycatchers in a study by Marchetti et al (1996). Silverin and Andersson (1984) found that ants (and other Hymenoptera) were the most common prey species delivered to the nestlings.…”
mentioning
confidence: 99%
“…Bibby and Green 1981, Berthold 1988, Alerstam and Hedenströ m 1998, Weber et al 1998. This is a time when selection pressures have almost certainly been strong, and the demands of migration are well reflected in species' morphology (Leisler and Winkler 1991, Winkler and Leisler 1992, Mö nkkö nen 1995, Marchetti et al 1996a, fattening strategies (Biebach 1992, Jenni-Eiermann andJenni 1994), food use Simons 1995, Bairlein 1998), energetics (Klaassen and Biebach 1994), physiology (Hume andBiebach 1996, Jenni andJenni-Eiermann 1998), moult strategies (Kaiser 1996), flight speed, routes (Fransson 1995) and other characteristics that may well be genetically determined (Berthold 1991, Berthold and Terrill 1991, Helbig 1996. But is it realistic to view the optimisation of migratory strategies only from these autecological perspectives?…”
mentioning
confidence: 99%